Use of three-way stopcock valves for maintaining safe cuff pressures in tracheostomised adult patients: a preliminary study - Rosales Lillo, Felipe Gonzalo; Alarcón Cuevas, Diego Alfredo (Revista de Investigación en Logopedia, 2025)
In vitro models have shown that disconnecting the cuffometer from the pilot balloon of artificial airway devices generates pressure losses. This may contribute to the passage of content into the lower airway, which increases the risk of aspiration pneumonia. The aim of this project is to determine if the use of three-way stopcock valves prevents the loss of cuff pressures when disconnecting the cuffometer from the pilot balloon in adult tracheostomised patients. A descriptive, observational and cross-sectional study was performed, which included a total of 10 hospitalised and tracheostomised subjects between April and July 2024, at the Hospital San Juan de Dios, Santiago, Chile. Three-way stopcock valves, analogue and digital cuffometers were used during the measurement procedure of three pressures: 20, 30 and 25 cmH2O (P1, P2 and P3). The initial inflation pressures and final pressures upon disconnection of the analogue cuffometer were registered. For this research, non-significant p values were considered favourable. This is because no statistical difference between initial and final cuff pressure after the disconnection of the analogue cuffometer was expected. The project was approved by a Research Ethics Committee. For P1, there was an initial and final pressure difference of .300 cmH2O; for P2 .500 cmH2O; and for P3 .000 cmH2O. There was no significant loss of cuff pressure when disconnecting the cuffometer from three-way stopcock valves. These valves could be effective for the management of patients with an artificial airway. It is mandatory to continue with this line of research.